Consumer Concern About Food Safety and Its Impact on Their Familiarity With Food Traceability Systems in China. Issue 1 (2nd January 2017) - Yu, Jianbin; Qiao, Juan
ABSTRACT: Consumer familiarity is critical in the promotion of food traceability systems. The authors used consumer survey data from four cities in China to conduct a quantitative investigation of consumer concern about food safety and its impact on the consumers' familiarity with food traceability systems. Statistical analysis and a Probit model were used, and the results show a high level of consumer concern about food safety. In contrast, consumers' familiarity with food traceability systems is very low. Consumers' concern about food safety significantly influences their familiarity with food traceability systems. In addition, consumers' age, work experiences related to the food industry, and habit of asking for food receipts or invoices all have significant influences on their familiarity with food traceability systems.